USAGE OF THE ANHARMONIC CORRELATED EINSTEIN MODEL TO DEFINE THE EXPRESSIONS OF CUMULANTS AND THERMODYNAMIC PARAMETERS IN THE CUBIC CRYSTALS WITH NEW STRUCTURE FACTORS - Ba Duc Nguyen (Наука и техника)
By using potential effective interaction in the anharmonic correlated Einstein model on the basis of quantum statistical theory with phonon interaction procedure, the expressions describing asymmetric component (cumulants) and thermodynamic parameters including the anharmonic effects contributions and by new structural parameters of cubic crystals has been formulated. This new parameters describing the distribution of atoms. The expansion of cumulants and thermodynamic parameters through new structural parameters has been performed.